2022
DOI: 10.1002/jpen.2330
|View full text |Cite
|
Sign up to set email alerts
|

Carbamazepine mitigates parenteral nutrition–associated liver disease in a novel ambulatory piglet model

Abstract: Background Parenteral nutrition (PN) remains a critical therapeutic option in patients who cannot tolerate enteral feeding. However, although lifesaving, PN is associated with significant side effects, including liver injury, the etiology of which is multifactorial. Carbamazepine (CBZ), an antiepileptic medication, is known to modulate hepatic fibrosis and hepatocellular injury in a variety of liver diseases. We hypothesized that CBZ could prevent PN‐associated liver disease (PNALD), which we tested by using o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Song et al investigated the effect of carbamazepine on a TPN piglet model. This antiepileptic and autophagy enhancer when combined with TPN vs. TPN alone led to a significant decrease in mean serum bilirubin, GGT, and cholestasis, as well as Ki67 expression ( P = 0.01), indicating that carbamazepine can potentially mitigate the severity of PNALD [22 ▪ ]. These studies show that FXR and autophagy regulators may be future therapeutic strategies for ameliorating the progression of IFALD.…”
Section: Pathophysiologymentioning
confidence: 76%
“…Song et al investigated the effect of carbamazepine on a TPN piglet model. This antiepileptic and autophagy enhancer when combined with TPN vs. TPN alone led to a significant decrease in mean serum bilirubin, GGT, and cholestasis, as well as Ki67 expression ( P = 0.01), indicating that carbamazepine can potentially mitigate the severity of PNALD [22 ▪ ]. These studies show that FXR and autophagy regulators may be future therapeutic strategies for ameliorating the progression of IFALD.…”
Section: Pathophysiologymentioning
confidence: 76%
“…Song et al hypothesized that this drug could also prevent the development of PNALD. A study on piglets was conducted and it was found that the administration of CBZ alleviated the severity of PNALD [48].…”
Section: The Therapeutic Strategiesmentioning
confidence: 99%
“…Song et al (2022) introduced supplementary oral carbamazepine (30 mg/kg/day) to piglets given TPN and observed a decrease in hepatic cholestatic deposits with CBZ treatment (12.5 ± 2.4, p = 0.038) vs. TPN animals (TPN 15.7 ± 2.2, p < 0.001). Additionally, elevated GGT levels in TPN (26.3 ± 6.9 IU/L) decreased when CBZ was introduced (19.8 ± 2.7 IU/L, p = 0.047) [ 117 ] ( Table 1 ).…”
Section: Novel Therapeutics ( Table 1 )mentioning
confidence: 99%